99 cent: Price Points in E-Commerce - Michael E. Kummer; Franz Hackl; Rudolf Winter-Ebmer (Verein für Socialpolitik, 2010)
Basu (2006) argues that the prevalence of 99 cent prices in shops can be explained with rational consumers who disregard the rightmost digits of the price. This bounded rational behaviour leads to a Bertrand equilibrium with positive markups. We use data from an Austrian price comparison site and find results highly compatible with Basu's theory. We can show that price points - in particular prices ending in 9 - are prevalent and have significant impact on consumer demand. Moreover, these price points are sticky; neither the price-setter itself wants to change them neither the rivals do underbid these prices, if they represent the cheapest price on the market.
Keywords: L11; D41; C41; 330